2017
DOI: 10.1038/ijo.2017.21
|View full text |Cite
|
Sign up to set email alerts
|

Decreased lipid metabolism but increased FA biosynthesis are coupled with changes in liver microRNAs in obese subjects with NAFLD

Abstract: This study confirms decreased liver glucose and lipid metabolism but increased FA biosynthesis coupled with changes in five unique miRNAs in obese patients with NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 60 publications
3
84
1
Order By: Relevance
“…This miRNA, belonging to the miR‐146 family along with miR‐146a, was shown to have a potential tumor‐suppressive role in HCC development and to be differentially expressed in inflammatory liver diseases . Furthermore, Xiang et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This miRNA, belonging to the miR‐146 family along with miR‐146a, was shown to have a potential tumor‐suppressive role in HCC development and to be differentially expressed in inflammatory liver diseases . Furthermore, Xiang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, autocrine IL‐6 stimulation of liver cancer progenitor cells has been described to promote malignant progression of HCC . Interestingly, the IL‐6‐induced miR‐146b‐5p was found to be up‐regulated during progression to steatosis and steatohepatitis in rats as well as in liver diseases (e.g., in obese subjects with non‐alcoholic fatty liver diseases (NAFLD) and in NASH patients). On the contrary, it has been shown that this miRNA (as well as miR‐146a‐5p) was reduced in HCC tumor tissues compared to the surrounding tissues, indicating a tumor‐suppressive role for this miRNA .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that the miR-30 family play an important role in adipocyte differentiation and fat synthesis [26]. A Spanish study conducted by Latorre et al showed that patients with NAFLD and obesity had lower miR-30b-5p level in the liver compared with simple obese patients, and the expression of miR-30b-5p was decreased in hepatocytes after stimulated with fatty acid in vitro [27]. Dai et al conducted a study in 2019 showed that higher level of serum miR-30b is correlated with the higher steatosis and HOMA-IR grade [28].…”
Section: Introductionmentioning
confidence: 99%
“…If a majority of miRNAs present in circulation of individuals with NAFLD originate from the liver, it would be reasonable to expect an increase in the expression of miR‐122 in hepatic parenchyma, along with a progression of NAFLD across its stages. However, in the diseased parenchyma of the livers of patients with NAFLD, intracellular levels of miR‐122 are lower than those in the livers of healthy individuals (Fig. A).…”
Section: Mir‐122: Intracellular–extracellular Seesaw Expression Paradoxmentioning
confidence: 93%